(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
Background: Clinacanthus nutans is recognized for extracts rich in phenolics and flavonoids, exhibiting noteworthy antioxidant and anti-inflammatory activities. Under pressurized hot water extraction (PHWE)—a green, water-only technique—both extraction settings and the specific plant tissue significantly influence the yield and integrity of these phytochemicals. Methods: We executed a head-to-head comparison of leaves and stems under unified PHWE screening parameters: 120 °C, 20 min, 2 g of sample in 50 mL of water, with a particle size of <63 μm. Measured outcomes included Total Phenolic Content (TPC), Total Flavonoid Content (TFC), and DPPH radical-scavenging activity. We further assessed the robustness of the extraction across varying solvent-to-solid ratios and sample-mass ranges while maintaining constant temperature and time to ensure the reliability of the tissue-specific findings.